Ali - ali? Ideologija in estetska kakovost v književni kanonizaciji - Van Peer, Willie (Primerjalna književnost, 1999)
Either - or? Ideology and aesthetic quality in literary canonization. - Traditional explanations of literary canonization usually involve two concepts: power and beauty. To some, the canon is the result of power conflicts, resulting in a text selection that is largely dominated by ideological content. Rejecting this view as a political simplification that has little to do with the nature of literature, others invoke aesthetic quality as the main criterion for a text's inclusion in the canon. In this article I will argue that this opposition is itself a misconstruction - although the ideological component plays a dramatically different role from what has been assumed by (neo-)Marxist and poststructuralist scholars. I will illustrate my argument with an analysis of the content and form of Shakespeare's Romeo and Juliet, as compared with its near-contemporary The Tragical Historye of Romeus and Juliet by Arthur Brooke. This analysis first follows a more traditional model of textual analzsis, which is thean further corroborated by an independent computer analysis of the same texts.
Keywords: literarna teorija; literary theory; literarni kanon; literarno vrednotenje; literarna estetika; angleška književnost